A feasibility study of application and potential effects of a single session transcranial direct current stimulation (tDCS) on competitive anxiety, mood state, salivary levels of cortisol and alpha amylase in elite athletes under a real-world competition - Mehrsafar, A. H.; Rosa, M. A. S.; Zadeh, A. M.; Gazerani, P. (Physiology & Behavior, 2020)
Objective: To examine feasibility and potential effects of a single session tDCS over the dorsolateral prefrontal cortex (DLPFC) on competitive anxiety, mood state, and autonomic and endocrine stress responses in elite archer athletes under a real world competition. Methods: Twelve male elite archers volunteered to participate in this pilot trial. Participants were randomized in order to take left anodal DLPFC, left cathodal DLPFC, or sham stimulation (the F3 or F4 areas according to the 10/20 EEG International System) in a within-subject study design. This study included three official competitions. About 45 min before the competition, the tDCS stimulation process was started and the participants were stimulated for 20 min with 2 mA current. Psychophysiological responses, including Brunel Mood Scale and Competitive state anxiety inventory-2-revied, were collected 15 min before each competition. Additionally, salivary cortisol (sCort) and salivary alpha-amylase (sAA) were collected 1 hour and 10 min before competition as well as 10 min and 1 hour after competition. Results: Findings demonstrated that anodal tDCS was feasible and could lead to enhance mood state (vigor, tension and fatigue) and a decrease in competitive anxiety, as compared to cathodal and sham stimulation (all p < 0.05). However, self-confidence remained unaffected by the tDCS (p > 0.05). Anodal stimulation resulted in a lower salivary cortisol and alpha-amylase response (all p < 0.05). Correlations between competitive anxiety and mood states with physiological stress markers (sCort and sAA) were not significant (all p > 0.05). Conclusions: The present study provides the first preliminary evidence that anodal tDCS over the DLPFC is feasible and could modulate competitive anxiety and physiological stress responses to the acute stress of competition (potentially by a top-down regulation of HPA and SAM systems as well as the vagal system). Findings support the notion that non-invasive brain stimulation might be advantageous to enhance sport performance under competitive situations. However, additional studies in a larger sample size and different sport activities are encouraged to substantiate the findings.